The Audiovisual Language of the Documentary Applied to Television Series: Rhetorical strategies and hybridisation between fiction and non-fiction in television. - Higueras-Ruiz, María José; Pérez-Rufí, José Patricio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This paper examines the application of the audiovisual language of documentary in television series. The main objective is to identify and analyse the documentary techniques present in fiction series. Once the stylistic conventions of the documentary have been identified, a formal audiovisual analysis is carried out on a sample of representative series. The results confirm that the series incorporate documentary strategies and stylistic conventions such as the hand-held camera, on-camera testimonies, voice-over, or the inclusion of archive material. These strategies provide an appearance of authenticity and veracity, and blur the boundaries between fiction and non-fiction.